Blast injury from locally manufactured "Hakka patas" - Chathula Ushari Wickramasinghe; Amal Nishantha Vadysinghe (Wolters Kluwer Medknow Publications, 2023)
Explosives are potentially harmful devices that can create an explosion by a rapid release of a pressurized gas consequent to a chemical reaction within the device. They can inflict a variety of injuries, due to the blast wave, fire, and shrapnel. The pattern and severity of injuries will be determined by various factors, including explosive potential and constituents such as shrapnel. Homemade explosive devices (HEDs) pose a further threat due to their volatile, unpredictable nature which can lead to accidental explosions. We present the case of a 28-year-old farmer who presented with extensive blast injury to the left hand from a "Hakka patas," a HED endemic to Sri Lanka. The injuries to his hand consisted of extensive soft tissue and muscle loss, and fractures of metacarpal bones with amputation of the first distal phalanx. Low-grade explosives such as "Hakka patas" have the potential to cause injury greater than expected due to their volatile, unpredictable nature, causing accidental explosions. This can injure unintended targets, resulting in grave consequences. The specific pattern described in low-grade explosive injuries will be important to differentiate other explosive-related injuries for medicolegal purposes.